2012
DOI: 10.1093/europace/eus345
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic interference with cardiac pacemakers and implantable cardioverter-defibrillators from low-frequency electromagnetic fields in vivo

Abstract: Magnetic fields with intensities as high as those used in this study are rare even in industrial working environments. In most cases, employees can return to work after implantation of a bipolar pacemaker or an ICD, after an appropriate risk assessment. Pacemakers programmed to unipolar configurations can cause danger to their users in environments with high electromagnetic fields, and should be avoided, if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
4
30
0
3
Order By: Relevance
“…Because the distance between the ICD and spinal cord stimulator was much shorter compared with the peripheral nerve stimulator or electroacupuncture sites, this supports the hypothesis that interference is more likely when the electromagnetic field from a neuromodulating device is in closer proximity to sensing electrodes of a pacemaker or ICD (10). Recent research has demonstrated bipolar ICDs or permanent pacemakers may be safely exposed to high intensity external magnetic fields without interference (11). Further study is needed to determine compatibility of cardiovascular implantable electronic devices with close proximity neurostimulation.…”
Section: Discussionsupporting
confidence: 54%
“…Because the distance between the ICD and spinal cord stimulator was much shorter compared with the peripheral nerve stimulator or electroacupuncture sites, this supports the hypothesis that interference is more likely when the electromagnetic field from a neuromodulating device is in closer proximity to sensing electrodes of a pacemaker or ICD (10). Recent research has demonstrated bipolar ICDs or permanent pacemakers may be safely exposed to high intensity external magnetic fields without interference (11). Further study is needed to determine compatibility of cardiovascular implantable electronic devices with close proximity neurostimulation.…”
Section: Discussionsupporting
confidence: 54%
“…21 Usually a magnetic flux density of 100 micro-Tesla is considered to be the safety level for pacemakers and ICDs, 22 and studies of static magnetic fields have shown that no changes in terms of rate or rhythm of the heart were seen in experiments with animals or humans with the use of up to 8 Tesla. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Scientists are trying to answer all calls for specific categories’ interaction with environmental or professional RF exposure. Geographical location [90,94,95], occupational groups [96,97], sections of the population [98] such as children and youngsters [99,100] or pregnant women [101] are only several elements that have been investigated in a cohort of voluntary subjects participating in research or clinical studies, or considered in informative epidemiologic meta-analysis [102] surveys. Moreover, the impacts of diagnostic devices such as magnetic resonance scanners that emit RF were analyzed [103].…”
Section: The Effects Of Rf Exposure On Humansmentioning
confidence: 99%